The characteristics of the housing market and the goal of stable and healthy development in China's cities - Guocheng Xiang; Juan Tang; Shuntian Yao (Journal of Risk and Financial Management, 2022)
This paper constructs a mathematical model to study China's urban real estate markets, in which there are different types of demands from house buyers, and housing suppliers adopt the strategy of quality differentiation second-degree price discrimination. Our theoretical result shows that, in China's case, without government intervention in the housing market, it is almost inevitable that the prices of both housing and the related resources will rocket. To achieve the goal of "houses built for inhabitance", we put forward a policy scheme to achieve "houses built for inhabitance" in China's cities from the perspectives of "speculation limitation" and "price control". We also conduct a numerical analysis to consider the macroeconomic effects of these two policy solutions on the housing market, and we conclude that Chinese authorities should introduce a resale tax in the housing market and learn from Singapore's experience in housing market regulation.
Keywords: 650; residential demand; speculative demand; quality differentiation; pro-rich; pro-poor